The educational values ​​included and proposed to be included in the geography book for the eighth grade of basic education in Jordan - Al-Habahbeh, Sultan Said (Journal of Educational and Psychological Sciences, 2021)
The aim of this research is to uncover the educational values ​​included in the geography book for the eighth grade in Jordan, and to present a number of values ​​proposed to be included in this book. The study population consisted of the geography book for the eighth grade in Jordan for the first and second semesters of the academic year (2020/2021), and the study population was determined. And based on the content analysis method, the analysis card was used to determine the values ​​available in the units of the geography book for the eighth grade in Jordan, and a classification was prepared for this study, consisting in its final form of (5) main areas, each of which included a number of sub-values, totaling (26) A sub-value, and the results showed that the total number of occurrences of educational values ​​included in the geography textbook for the eighth grade in Jordan is (301) repeatedly, and the national sphere came first with a total of (91) iterations, and a percentage (30.23%) of the total occurrences of educational values. The educational field came in second place, with a total of (80) recurrences and a percentage (26.58%). And in the third place, the religious field came with a total of 51 times and a percentage of (16.94%). As for the social field, it ranked fourth with a total of 45 recurrences and a percentage of 14.95%. The ethical field came in fifth place, with a total of 34 recurrences, and a percentage of (11.30%). It is also noticed through the data in Table (4) that the educational values ​​included in the geography book for the eighth grade for the first semester of the first semester totaled (115) recurrences with a percentage of (38.21%), and for the second semester the total values ​​were (186) iterations. By a percentage (61.79%). The supervisors and some teachers suggested adding some values, which were found suitable for the age group from their point of view, and being the closest to this group of students. Those values ​​were fixed, and the number of values ​​suggested by the educational supervisors and teachers of the eighth grade of basic geography reached (19) value, It is distributed over the first and second semesters, where the number of values ​​for the first semester reached (9) suggested educational values, and (10) values ​​for the second semester of the book. It is noted on the educational values ​​that they emanate from the daily life of the Jordanian citizen.The researcher recommended the necessity of adopting advance planning based on scientific methods in setting educational values ​​in the geography book for the eighth grade. And the introduction of the educational values ​​proposed by educational supervisors and social education teachers, as they are not mentioned in the geography book for the eighth grade, and are compatible with the requirements of the age and the target age group.
Keywords: educational values; geography; eighth grade